Mean Expression of the X-Chromosome is Associated with Neuronal Density - Swingland, James T.; Durrenberger, Pascal F.; Reynolds, Richard; Dexter, David T.; Pombo, Ana; Deprez, Manuel; Roncaroli, Federico; Turkheimer, Federico E. (Frontiers in Neuroscience, 2012)
Neurodegenerative diseases are characterised by neuronal loss. Neuronal loss causes a varying density of neurons across samples which confounds results from gene expression studies. Chromosome X is known to be specifically important in brain. We hypothesised the existence of a chromosomal signature of gene expression associated with the X-chromosome for neurological conditions not normally associated with that chromosome. The hypothesis was investigated using microarray datasets from studies on Parkinson's disease, Alzheimer's disease and Huntington's disease. Data were analysed using Chromowave, an analytical tool for detecting spatially extended expression changes across chromosomes. To examine associations with neuronal density, expressions from a set of neuron specific genes were extracted. The association between these genes and the expression patterns extracted by Chromowave was then analyzed. We observed an extended pattern of low expression of ChrX consistent in all the neurodegenerative disease brain datasets. There was a strong correlation between mean ChrX expression and the pattern extracted from the autosomal neuronal specific genes, but no correlation with mean autosomal expression. No chromosomal patterns associated with the neuron specific genes were found on other chromosomes. The chromosomal expression pattern was not present in datasets from blood cells. The ChrX:Autosome expression ratio was also higher in neuronal cells than in tissues with a mix of cell types. The results suggest that a loss of neurons manifests in gene expression experiments primarily as a reduction in mean expression of genes along ChrX. The most likely explanation for this finding relates to the documented general up-regulation of ChrX in brain tissue which, this work suggests, occurs primarily in neurons. The purpose and mechanisms behind this cell specific higher expression warrant further research, which may also help elucidate connectio